Aprendo en casa: Elaboramos encuestas, organizamos los datos en tablas de frecuencia y representamos en grficos estadsticos - Ordoez Parrilla, Leybi Teresa (2022)
The present work of professional assessment entitled "I learn at home: We elaborate surveys, we organize the data in tables of frequency and we represent in statistical graphics" has been elaborated for the students of second degree of Regular Basic Secondary Education of the educational institution "Our Lady of the ?Perpetuo Socorro" of Piura, with the purpose of developing the competence solve problems of data management and uncertainty, the statistics is part of it, which allows to provide solution to situations of the students environment to solve real problems; it also promotes critical reasoning, based on the valuation of evidence, supported by data, where graphs, statistical tables, summaries or statistical concepts appear._x000D_ Statistics is also a good vehicle for achieving communication skills, problem solving, cooperative and group work, helping students understand and value the role of statistics in society, incorporating its different fields of application in their daily work._x000D_ Throughout history, statistics have developed from a utilitarian practical view of solving problems of the moment such as knowing the number of inhabitants among other data; until arriving at the present time with the use of sophisticated instruments as elementary techniques of data collection to obtain information on phenomena and situations of their environment; representing it graphically and numerically, and forming a judgment about it, based on statistical concepts such as population, sample, sampling, variables, graphical representation, data tables, types of statistical graphics: bar charts, linear diagrams._x000D_ Nowadays, teachers have a constructivist conception of mathematics, that is why it directs the student to solve problems of the context competently, i.e., to articulate knowledge, skills and attitudes in a responsible and ethical manner. Therefore, the learning sessions are developed in the context of distance education from a teaching role as a mediator, where he provides information in a timely and orderly manner in which the student can interact with the teacher and classmates, with the material and the information provided, culminating the sessions with a challenge posed which constitutes evidence of learning._x000D_ The work is oriented towards formative evaluation whose purpose is for students to be autonomous in their learning by becoming aware of their weaknesses, needs and strengths; the teachers aim is to attend the different learning needs of the students by providing opportunities according to the levels reached by each one in order to reduce gaps, avoid backwardness and exclusion.